ACACIA CATACHU GUM IN SITU FORMING GELS WITH PROLONGED RETENTION TIME FOR OCULAR DRUG DELIVERY - SINGH, MANDEEP; DEV, DHRUV (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The object is to study acacia catechu gum in situ, forming gels with prolonged retention times for ocular drug delivery. Methods: This study was sample collection and extraction, pre-formulation research, drug melting point and solubility preparation of standard stock solution, lambda max determination, and preparation of ciprofloxacin hydrochloride in situ gel. Results: The melting point of ciprofloxacin hydrochloride was found to be 290°C. The solubility of ciprofloxacin hydrochloride in pH 2.0 and pH 6.8 media is 7.88 0.005 mg/ml and 0.080 0.05 mg/ml. The max of ciprofloxacin hydrochloride was found to be 276–277 nm in simulated tear fluid pH 7.4. Prepared in situ gelling systems were evaluated for interaction studies to ensure that no interaction occurred between drugs and polymers. The pH of the formulations was found to be 7.1–7.4, and the drug content was in the range of 92–98%. All the prepared in situ gelling systems were evaluated for sterility. After 7 days of incubation, the results showed no microbial growth in all formulations. Conclusion: The developed formulation is a viable alternative to the conventional eye drops by virtue of its ability to enhanced bioavailability through its longer precorneal residence time.